Lactobacillus casei Variety rhamnosus Probiotic Preventively Attenuates 5-Fluorouracil/Oxaliplatin-Induced Intestinal Injury in a Syngeneic Colorectal Cancer Model - Chang, Ching-Wei; Liu, Chia-Yuan; Lee, Hung-Chang; Huang, Yen-Hua; Li, Li-Hui; Chiau, Jen-Shiu Chiang; Wang, Tsang-En; Chu, Cheng-Hsin; Shih, Shou-Chuan; Tsai, Tung-Hu; Chen, Yu-Jen (Frontiers in Microbiology, 2018)
Adjuvant 5-fluorouracil (5-FU)-based chemotherapy, including FOLFOX (5-FU, leucovorin, and oxaliplatin), is recommended for colorectal cancer. However, intestinal mucositis remains a common adverse effect for which no effective preventive strategies are available. To develop a convenient and novel way to alleviate mucositis, we investigated the effect of Lactobacillus casei variety rhamnosus (Lcr35) on FOLFOX-induced mucosal injury. BALB/c mice subcutaneously injected with syngeneic CT26 colorectal adenocarcinoma cells were orally administered Lcr35 daily before, during, and after 5-day injection of FOLFOX regimen, for 14 days. The following methods were used: diarrhea score for toxicity, ELISA for cytokine production, histopathology for intestinal injury, immunohistochemistry for apoptosis/proliferation and regulatory proteins, RT-PCR for cytokine mRNA expression, and DNA sequencing for fecal gut microbiota. FOLFOX administration to colorectal cancer-bearing mice significantly inhibited tumor growth and the accompanying marked diarrhea and intestinal injury histologically characterized by the shortening of villi and destruction of intestinal crypts. Preventive administration of Lcr35 dose-dependently reduced the severity of diarrhea and intestinal mucositis without affecting the anti-tumor effect of FOLFOX. The numbers of apoptotic, NF-κB-, and BAX-activated cells increased after FOLFOX, and these responses were mitigated by Lcr35. TNF-α and IL-6 upregulation by FOLFOX treatment was attenuated by Lcr35. The fecal gut microbiota composition of Firmicutes and Bacteroidetes disturbed by FOLFOX was significantly reversed by Lcr35 towards a preferential profile. In conclusion, the oral probiotic Lcr35 prevented FOLFOX-induced intestinal mucositis in colorectal cancer-bearing mice. The putative mechanism might involve modulation of gut microbiota and proinflammatory responses with suppression of intrinsic apoptosis in intestinal injury. Keywords: FOLFOX; Lactobacillus; intestinal mucositis; apoptosis; gut microbiota